LOCAL WISDOM OF THE ACEH COMMUNITY IN PEOPLE'S STORIES IN PIDIE AND PIDIE JAYA DISTRICTS - Junaidi Junaidi; Mujiburrahman Mujiburrahman; Vera Wardani (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2023)
There are many legendary folktales in Acehnese society; in particular, the folktales that developed in Pidie and Pidie Jaya contain messages about the local wisdom values of the Acehnese people. The value of the local wisdom of the Acehnese people in the folklore of Pidie and Pidie Jaya is described using a descriptive-qualitative approach and method and literature analysis techniques. Sources of research data are stories from Masyik Leun and Mat Usop (from Pidie) and stories from Biring Karnani (from Pidie Jaya). The stages of data collection started with reading the story script, followed by tagging and coding to be used as data, and further analyzed. Furthermore, the collected data was analyzed in stages; describe data, analyze data, classify data, and draw conclusions. Based on the results of the analysis, the local wisdom values contained in the Masyik Leun and Mat Usop stories and the Biring Karnani stories are divided into four types of local wisdom values. (1) Local wisdom values related to ethics, consist of: a) a person tries to change other people's wrong views, b) a grandmother always protects and loves her grandchildren, and c) a person must be responsive to all problems and trials. (2) The value of local wisdom regarding aesthetics or beauty is that Teungku Imum handed over ranup pate as a birthday invitation to residents of neighboring villages. (3) Local wisdom values related to religion or religion, consisting of a) the community fardhukifayah for those who died and b) the residents bringing home and eating the birthday rice from the place where the mauled ceremony was held. (4) Local wisdom values related to social inclusion include; a) residents use traditional tools as provisions on the road, b) everyone will find out the price of goods in the market, c) the community announces news of people who died in the public after dawn prayers, d) mawah efforts to help poor villagers, and e) everyone helps the villagers themselves by providing decent jobs.Ada banyak cerita rakyat yang melegenda dalam masyarakat Aceh; khususnya cerita rakyat yang berkembang di Pidie dan Pidie Jaya mengandung pesan tentang nilai kearifan lokal masyarakat Aceh. Nilai kearifan lokal masyarakat Aceh dalam cerita rakyat Pidie dan Pidie Jaya dideskripsikan dengan menggunakan pendekatan deskriptif-kualitatif dan metode serta teknik analisis literatur. Sumber data penelitian adalah cerita dari Masyik Leun dan Mat Usop (dari Pidie) dan cerita dari Biring Karnani (dari Pidie Jaya). Tahapan pengumpulan data dimulai dengan membaca naskah cerita, dilanjutkan dengan penandaan dan pengkodean untuk dijadikan data, dan selanjutnya dianalisis. Selanjutnya data yang terkumpul dianalisis secara bertahap; mendeskripsikan data, menganalisis data, mengklasifikasikan data, dan menarik kesimpulan. Berdasarkan hasil analisis, nilai kearifan lokal yang terkandung dalam cerita Masyik Leun dan Mat Usop dan cerita Biring Karnani terbagi menjadi empat jenis nilai kearifan lokal. (1) Nilai-nilai kearifan lokal yang berkaitan dengan etika, terdiri dari: a) seseorang berusaha mengubah pandangan salah orang lain, b) nenek selalu melindungi dan menyayangi cucunya, dan c) seseorang harus tanggap terhadap segala masalah dan cobaan. (2) Nilai kearifan lokal mengenai estetika atau keindahan yaitu Teungku Imum menyerahkan ranup pate sebagai undangan ulang tahun kepada warga desa tetangga. (3) Nilai-nilai kearifan lokal yang berkaitan dengan religi atau religi, terdiri dari a) fardhukifayah masyarakat bagi yang meninggal dan b) warga membawa pulang dan memakan nasi ulang tahun dari tempat diadakannya upacara maulid. (4) Nilai-nilai kearifan lokal yang terkait dengan inklusi sosial meliputi; a) warga menggunakan alat tradisional sebagai bekal di jalan, b) setiap orang akan mengetahui harga barang di pasar, c) masyarakat mengumumkan berita orang yang meninggal di depan umum setelah sholat subuh, d) upaya mawah membantu warga desa yang miskin, dan e) setiap orang membantu warga desa sendiri dengan memberikan pekerjaan yang layak.